Dentigerous Cyst Mimicking Odontogenic Keratocyst: A Rare Case Report with 12 Month Follow up - Rose M Joseph; Subhagatha Chakraborty; Anupama Nayak P; Dharnappa Poojary; Ashwin Rao; Nandita KP; Karuna YM (Indian Journal of Forensic Medicine & Toxicology, 2021)
Dentigerous cyst is one of the most commonly seen odontogenic cyst in children. It is characterized by aunilocular radiolucent lesion that encloses permanent tooth buds. Buccal bony expansion and a missing toothis the most common clinical feature. Various treatment modalities have been mentioned in the literature formanagement of dentigerous cysts. This case report presents the management of a left mandibular dentigerouscyst in a 10-year-old boy by surgical enucleation and its follow up.